2004
DOI: 10.1158/0008-5472.can-04-0250
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Receptor α in Human Breast Carcinoma as a Potent Prognostic Factor

Abstract: Estrogen-related receptor ␣ (ERR␣) was identified as a gene related to estrogen receptor ␣ (ER␣) and belongs to a class of nuclear orphan receptors. ERR␣ binds to estrogen responsive element(s) (ERE) and is considered to be involved in modulation of estrogenic actions. However, biological significance of ERR␣ remains largely unknown. Therefore, we examined the expression of ERR␣ in human breast carcinoma tissues using immunohistochemistry (n ‫؍‬ 102) and real-time reverse transcription-PCR (n ‫؍‬ 30). ERR␣ imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
214
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(225 citation statements)
references
References 49 publications
11
214
0
Order By: Relevance
“…There is mounting clinical evidence linking ERR␣ expression to tumor progression and less favorable prognoses in breast cancer patients (43,44,46,47). We have previously demonstrated that estrogens induce ERR␣ expression in MCF-7 cells, an ER␣-positive breast cancer cell line.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There is mounting clinical evidence linking ERR␣ expression to tumor progression and less favorable prognoses in breast cancer patients (43,44,46,47). We have previously demonstrated that estrogens induce ERR␣ expression in MCF-7 cells, an ER␣-positive breast cancer cell line.…”
Section: Discussionmentioning
confidence: 92%
“…The association of ERR␣ expression in breast cancer with a poor clinical outcome suggests it plays a role in tumor progression and aggressiveness (43,44,46). Evidence of similar correlates that appear in cancers of the prostate (79), ovary (80), colon (81), and endometrium (82) continue to emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11), a marker of tumor aggressiveness. Suzuki et al (12) reported that f55% of human breast cancers are positive for ERRa by immunohistochemistry, with ERRapositive status being associated with greatly increased risk of recurrence and adverse clinical outcome. Thus, ERRa shows potential as a prognosticator and target for breast cancer therapy, with ERRa possibly playing an important role by substituting for ERa activities, especially in ErbB2-positive, ERa-negative, and tamoxifen-resistant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Further, ERRa is now established to be associated with unfavorable biomarkers in human breast cancer. [19][20][21] Much less is known, however, about the extent or pattern of ERRa expression in the prostate. 22 The present study evaluated ERRa expression in human prostate tissues and PC cell lines by immunohistochemistry and Western blot analysis to assess its clinical significance.…”
mentioning
confidence: 99%